Speed and agility as predictors of long jump performance of male athletes - Mukesh Kumar Mıshra; Vishan Singh Rathore (Türk Spor ve Egzersiz Dergisi)
The main purpose of this study was to predict the long jump performance on the basis of speed, agility, height and weight of male athletes. 46 male athletes were participated in present study (mean ± SD; 22.28 ± 1.3770 years). The selected athletes were measured of their speed by 50m dash sprint test (sec.), agility measured by 4 x 10m shuttle run test (sec.) and long jump performance measured by long jump (meter). Pearson product-moment correlations revealed a significant negative correlation of Long Jump performance with speed (r = - 0.813, p lt; 0.05), Agility (r = - 0.702, p lt; 0.05) and weight (r = - 0.343, p lt; 0.05). Multiple correlations revealed that joint contribution of all independent variables to estimating Long Jump performance (R = .847, R2=.717), which impales that 71.7% of Long Jump Performance is obtained by these variables (Weight, Height, Agility and Speed). The regression analysis (enter method) outcomes proved that long jump performance can be determined by selected independent variables (F=25.933, p lt;0.05). Based on the result of present study suitable formula was determined [Long Jump performance = 5.356 -.283 (Speed) -.102 (Agility) + .021 (Height) -.019 (Weight)]. It was concluded that the formula suggested in this study, can be used to determine the long jump performance of male athletes.